The potential of large woody debris to alter biogeochemical processes and ecosystem services in lowland rivers. (22nd February 2014) - Krause, S.; Klaar, M. J.; Hannah, D. M.; Mant, J.; Bridgeman, J.; Trimmer, M.; Manning‐Jones, S.
<x xml:space="preserve">Abstract</x> River restoration and management practice promotes the (re)introduction of large woody debris (LWD) to support ecosystem services in lowland streams, such as the buffering of thermal extremes or enhanced nutrient attenuation. However, influences of LWD on spatial patterns and temporal dynamics of groundwater–surface water exchange fluxes, sediment transport and deposition, biogeochemical cycling, thermal patterns, and ecohydrological process dynamics are not yet fully understood. This study reviews research on the implications of interacting hydrodynamic and hydrostatic forcings on different types of LWD structures and their consequences for streambed residence time distributions, thermal conditions, and biogeochemical cycling. It analyzes the implications of LWD on structural heterogeneity in physical and chemical properties of lowland river streambed and provides an outlook of how enhanced nutrient loading of agricultural lowland rivers can be ameliorated by LWD‐induced increase of biogeochemical turnover. Based on the analysis of the potential implications of different LWD structures, this study highlights how imminent research gaps can be overcome by integrating novel experimental and modeling technologies across traditional subject boundaries in order to provide robust scientific evidence of the efficiency of LWD in river restoration and management. Conflict of interest: The authors have declared no conflicts of interest for this article.